The Role of Educators in Facing the Digital Era Through Innovative Learning in PPKN Subjects - Wiratama, Muhammad Rafsan; Rusydi, Ibnu; Japar, Muhammad (CV. Rayyan Dwi Bharata, 2024)
This article discusses the transformation of the educational landscape due to innovation and technology in the digital era. Presents an analysis of the use of new learning models to improve teacher competency in the digital era, as well as challenges and solutions in adopting innovative learning, especially in Pancasila and Citizenship Education (PPKn) subjects. Through a literature review method, this article identifies innovative strategies, required teacher competencies, and challenges faced, such as lack of resources and technology skills. The results emphasize the importance of increasing teacher competency, technology integration, and collaborative support to create innovative learning environments in the digital era.